Canadian Cases in Public International Law in 2006–7 / Jurisprudence canadienne en matière de droit international public en 2006–7 - Ert, Gibran van (Canadian Yearbook of International Law, 2008)
Evidence — letters rogatory — public policy against extraterritorial applications of US lawMorgan, Lewis & Bockius LLP v. Gauthier (2006), 82 OR (3d) 189 (29 August 2006). Ontario Superior Court of Justice.The applicant MLB was a US law firm carrying on business principally in Philadelphia. It sought an order from the Ontario Superior Court of Justice giving effect to a letter of request issued by the Court of Common Pleas of Philadelphia County, Pennsylvania. This court sought the assistance of the Ontario court in obtaining document production and testimony from the respondent, Claude Gauthier, a Canadian citizen resident in Ontario.